Holocene reef growth in the tropical southwestern Atlantic: Evidence for sea level and climate instability. (15th August 2019) - Dechnik, Belinda; Bastos, Alex C.; Vieira, Laura S.; Webster, Jody M.; Fallon, Stewart; Yokoyama, Yusuke; Nothdurft, Luke; Sanborn, Kelsey; Batista, Joao; Moura, Rodrigo; Amado-Filho, Gilberto
Abstract: The Holocene epoch offers a potential analogue for understanding future sea-level variability as both SST's and Global Mean Sea Levels (GMSL) were at times higher than observed today. However, GMSL can differ significantly from Relative Sea Level (RSL), even at far-field sites remote from margins of former ice sheets. Much of this spatial variability has been shown to be consistent with the predictions of glacial isostatic adjustment (GIA) models. Whilst it is generally accepted that RSL at far-field sites reached its maximum during the mid-Holocene, there have been many interpretations of sea level fall following the highstand from ∼6 ka. Here, we present a RSL history from several tectonically stable, far-field sites in eastern Brazil, derived from 17 microatoll and 45 fossil reef flat ages. Our results show evidence for two periods of RSL instability during the Holocene which differ from GIA predictions, including a hiatus in reef growth ∼3.7–2.5 ka. These results are broadly synchronous with several other locations in the Southern Hemisphere suggesting global rather than regional climatic forcing mechanisms are responsible. Variations in SST and southern hemisphere ice sheet dynamics are proposed as possible controlling mechanisms for the observed RSL oscillations beginning at ∼3.7 ka and 2 ka respectively. We suggest that these global processes combined with increased precipitation (and higher sediment flux) from several regional climatic forces created inhospitable conditions for reef growth, contributing to the observed hiatus and reduced reef flat accretion during the late Holocene (∼2 ka to present). Highlights: We report the lowest Holocene sea level highstand for the south eastern Brazilian region. Two relative sea level oscillations identified at ∼3.7 ka and 2 ka respectively. Hiatus in reef flat growth identified from 3.7 to 2.5 ka.